Novos elementos pós-clássicos do anfiteatro de Conimbriga - De Man, Adriaan (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
After a number of previous interventions at the building, a new excavation was carried out in the amphitheatre’s south sector, where the Late Roman wall was superposed, as part of a larger historical change. A significant fourth century sequence was detected in straight articulation with this architectonical shift, leading to the comprehension of several Early Medieval domestic occupations.